Frequency, Risk Factors, and Prognosis of Dehydration in Acute Stroke - Cortés-Vicente, Elena; Guisado-Alonso, Daniel; Delgado-Mederos, Raquel; Camps-Renom, Pol; Prats-Sánchez, Luis; Martínez-Domeño, Alejandro; Martí-Fàbregas, Joan (Frontiers in Neurology, 2019)
Objective. To determine the frequency, risk factors and impact on the outcome of dehydration after stroke. Methods. In this cross-sectional observational study, we included prospectively and consecutively patients with ischemic and hemorrhagic stroke. The serum Urea/Creatinine ratio (U/C) was calculated at admission and 3 days after the stroke. Dehydration was defined as U/C>80. Patients were treated in accordance with the standard local hydration protocol. Demographic and clinical data were collected. Neurological severity was evaluated at admission according to the NIHSS score; functional outcome was assessed with the modified Rankin scale score (mRS) at discharge and 3 months after the stroke. Unfavourable outcome was defined as mRS>2. Results. We evaluated 203 patients; 78.8% presented an ischemic stroke and 21.2% a hemorrhagic stroke. The mean age was 73.4 years ±12.9; 51.7% were men. Dehydration was detected in 18 patients (8.9%), 9 patients at admission (4.5%) and 9 patients (4.5%) at 3 days after the stroke. Female sex (OR 3.62, 95%CI 1.13-11.58, p=0.03) and older age (OR 1.05, 95%CI 1-1.11, p=0.048) were associated with a higher risk of dehydration. Dehydration was associated with an unfavourable outcome at discharge (OR 5.16, 95%CI 1.45-18.25, p=0.011) and with a trend to a higher risk of an unfavourable outcome after 3 months (OR 2.95, 95%CI 0.83-10.48, p=0.095). Conclusion. Dehydration is a treatable risk factor of a poor functional outcome after stroke that is present in 9% of patients. Females and elders present a higher risk of dehydration.